The Lord of the Ice Garden Jarosław Grzędowicz’s as a Praise of Freedom - Poradecki, Mateusz (Lustro, 2020)
The article presents Jarosław Grzędowicz’s novel Pan Lodowego Ogrodu [The Lord of the Ice Garden] from the perspective of considerations concerning freedom. Planet Midgaard is a mirror reflection of Earth’s civilisation, a reflection that allows for the analysis of totalitarian systems – their mechanisms and causes of emergence. The hero of the novel perceives threats to freedom not only in murderous regimes, but he also warns against excessive “protectiveness” of the state towards its citizens and the development of technology which leads to absolute control over man.